Analisis Implementasi Penyajian Laporan Keuangan dan Pelaporan Pajak Berbasis Aplikasi Pada CV Afiq Intan Perwira - Sandra, Elminaliya; Mustika, Ita (STIKOM Tunas Bangsa Pematangsiantar, 2023)
The purpose of this study is the author wants to know what happens when ABSS Accounting and taxation is implemented, whether the implementation of information systems in presenting financial and tax reports encounters many obstacles or not, can have a positive impact or even have a negative impact after using the software and know the implementation of tax applications. The data collection method is data obtained directly from the company, namely by interviews and observations on related parts of the company, the author conducted interviews with employees of CV Afiq Intan Perwira. In analyzing the data that has been obtained this research is a field research category (field research), so the authors use qualitative and descriptive methods. The result of the research is that the accounting system that will be implemented is ABSS Accounting, which is a more adequate and reliable accounting system than using Microsoft Excel. Electronic tax reporting can make it easier to report periodical and annual SPTs for both corporate SPTs and other SPTs. So that it can increase the knowledge of CV Afiq Intan Perwira so that as a taxpayer it can make it easier to report. What makes the implementation of an accounting information system based on ABSS Accounting and taxation can be of benefit to CV Afiq Intan Perwira because it has complete features that make it easier for users compared to the previous system.